Historical and pedagogical aspects of the problem of harmonization of intellectual and emotional components in the structure of personality (Pedagogy of Higher and Secondary Education, 2011)
An attempt to clarify some peculiar features of solving problem of harmonization of intellectual and emotional aspects.
Keywords: history-and-pedagogy concepts; harmonization; intellect; emotions; personality of a child